Anisotropic phenolic aerogel composite material and preparation method thereof
By improving the interface dispersion and directional freeze-drying technology between water and phenolic resin, an orderly anisotropic pore structure is constructed, which solves the shortcomings of phenolic aerogel materials in directional mass transfer and heat transfer functions, and expands its application scope And achieved green preparation.
Patent Information
- Application Number
- CN202410794423.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-06-19
AI Technical Summary
The disordered nanopore structure of existing phenolic aerogel materials limits its implementation of directional mass transfer, heat transfer and other functions, and cannot expand its application range.
The surfactant is used to improve the interface dispersion between water and phenolic resin, and an ordered anisotropic pore structure is constructed through directional freezing and freeze-drying technology, and the curing temperature is reduced by curing accelerator to form a phenolic aerogel with directional conduction properties. Composite material.
It overcomes the problem that traditional phenolic aerogels cannot achieve directional mass transfer and heat transfer functions, expands its application prospects in the fields of ion conductors, environmental purification, filtration and energy catalysis, and achieves green preparation.
Smart Images

Figure CN118652518B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to an anisotropic phenolic aerogel composite material and a preparation method thereof. Background Art
[0002] Phenolic resin aerogel has a unique microstructure with inherent cross-linking and high rigidity network, and is a promising material in adsorption, separation, catalysis, energy conversion and storage. Since Pekala RW first synthesized phenolic resin aerogel in 1989, researchers have made great progress in phenolic resin aerogel, which has been widely used as thermal insulation material in the aerospace field.
[0003] Due to the characteristics of the molecular structure, existing phenolic aerogels are generally prepared by a sol-gel polymerization reaction mechanism, followed by solvent replacement and normal pressure drying. However, this method prepares a phenolic aerogel composite material based on an isotropic nanoporous structure formed by the accumulation of nanoparticles. The internal pore structure of the aerogel is in a disordered state. This disordered pore structure aerogel cannot achieve directional mass transfer, heat transfer and other functions, which has certain limitations on broadening its application and improving its performance. Summary of the invention
[0004] In view of one or more technical problems existing in the prior art, the present invention provides an anisotropic phenolic aerogel composite material and a preparation method thereof. The aldehyde resin aerogel matrix in the phenolic aerogel composite material provided by the present invention is a phenolic aerogel with an anisotropic nanopore structure, which has better orientation structure and anisotropy, can realize directional conduction of heat, overcomes the problem that the isotropic traditional phenolic aerogel formed by internal disordered nanoparticle accumulation cannot realize directional mass transfer, heat transfer and other functions, breaks through the limitation that it cannot be applied and developed in the field of directional mass transfer and transmission, greatly expands the application scope of phenolic aerogel, and has broad application prospects in the fields of ion conductors, environmental purification, filtration and energy catalysis.
[0005] The present invention provides a phenolic aerogel composite material in a first aspect. The anisotropic phenolic aerogel composite material comprises a phenolic aerogel matrix and a fiber reinforcement. The phenolic aerogel matrix is a phenolic aerogel with an anisotropic nanoporous structure.
[0006] Preferably, the phenolic aerogel precursor for preparing the phenolic aerogel matrix comprises a water-soluble phenolic resin, a surfactant, a curing agent, a curing accelerator and water; preferably, the content of the water-soluble phenolic resin in the phenolic aerogel precursor is not more than 10 wt %.
[0007] Preferably, the mass ratio of the water-soluble phenolic resin to water is 1 to 8:60;
[0008] The mass ratio of the surfactant to water is 1 to 6:30;
[0009] The mass ratio of the curing agent to the water-soluble phenolic resin is 0.5 to 2:5; and / or
[0010] The mass ratio of the curing accelerator to the water-soluble phenolic resin is 0.1 to 0.5:1.
[0011] Preferably, the solid content of the water-soluble phenolic resin is 60-70 wt %; and / or
[0012] The water-soluble phenolic resin is a phenolic prepolymer with a molecular weight of 200 to 800;
[0013] Preferably, the surfactant is a cationic active agent, preferably at least one of cetyltrimethylammonium bromide and cetyltrimethylammonium chloride.
[0014] Preferably, the curing agent is a silane coupling agent, preferably at least one of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-mercaptopropyltriethoxysilane and vinyltriethoxysilane.
[0015] The curing accelerator is bicarbonate, preferably at least one of sodium bicarbonate and potassium bicarbonate.
[0016] Preferably, the fiber reinforcement is at least one of chopped fibers, a carbon fiber preform, a quartz fiber preform, a mullite fiber preform, a glass fiber preform, and a porous mullite fiber skeleton; and / or
[0017] The fiber reinforcement is at least one of fiber felt, 2D woven cloth, 2.5D fabric, and 3D fabric.
[0018] In a second aspect, the present invention provides a method for preparing the anisotropic phenolic aerogel composite material according to the first aspect, the preparation method comprising the following steps:
[0019] The fiber reinforcement is impregnated in a phenolic aerogel precursor, and then pre-frozen, freeze-dried and solidified to obtain a phenolic aerogel composite material.
[0020] Preferably, the impregnation is vacuum impregnation;
[0021] The freeze drying temperature is -60 to -18°C, and the freeze drying time is 20 to 35 hours; the solidification temperature is 30 to 50°C, and the time is 15 to 40 hours; and / or
[0022] After the curing, the method further includes the steps of washing and drying.
[0023] Compared with the prior art, the present invention has at least the following beneficial effects:
[0024] The aldehyde resin aerogel matrix in the phenolic aerogel composite material provided by the present invention is a phenolic aerogel with an anisotropic nanopore structure inside, so it has better orientation structure and anisotropy, can realize directional conduction of heat, overcomes the problem that the disordered hole structure inside the traditional phenolic aerogel structure of isotropic nanopore structure formed by nanoparticle accumulation cannot realize directional mass transfer, heat transfer and other functions, and breaks through the limitation that it cannot be applied and developed in the field of directional mass transfer and transmission. At the same time, by compounding the phenolic aerogel matrix and the fiber reinforcement, the contradiction between the high porosity, high specific surface area and high compressive strength of the phenolic aerogel is solved, and the application range of the phenolic aerogel is greatly expanded, and it has a wide application prospect in the fields of ion conductors, environmental purification, filtration and energy catalysis.
[0025] The present invention first improves the interfacial dispersibility of water and phenolic resin based on a surfactant, then phase-separates the phenolic resin from water along the growth direction of the ice crystal microchannel through directional freezing, and then removes the ice template through a freeze-drying technology to achieve the construction of an ordered anisotropic pore structure. Finally, a curing accelerator is used to reduce the curing temperature of the phenolic resin and perform low-temperature curing, thereby avoiding the collapse of the pore structure due to too high a curing temperature during the curing process. Finally, a phenolic aerogel composite material with an ordered anisotropic phenolic aerogel structure is obtained, thereby improving the directional heat conduction performance of the phenolic aerogel composite material and overcoming the problem that traditional phenolic aerogels cannot achieve directional mass transfer, heat transfer and other functions.
[0026] The preparation method of the invention has simple process, adopts a water dispersion system, has no pollution to the environment, and realizes the green preparation of the anisotropic phenolic aerogel composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 This is a preparation flow chart of an anisotropic phenolic aerogel composite material provided by the present invention;
[0029] Figure 2 This is a scanning electron microscope of the anisotropic phenolic aerogel composite material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] The present invention provides a phenolic aerogel composite material in a first aspect. The anisotropic phenolic aerogel composite material comprises a phenolic aerogel matrix and a fiber reinforcement. The phenolic aerogel matrix is a phenolic aerogel with an anisotropic nanoporous structure.
[0032] The aldehyde resin aerogel matrix in the phenolic aerogel composite material provided by the present invention is a phenolic aerogel with an anisotropic nanopore structure inside, so it has better orientation structure and anisotropy, can realize directional conduction of heat, overcomes the problem that the disordered hole structure inside the traditional phenolic aerogel structure of isotropic nanopore structure formed by nanoparticle accumulation cannot realize directional mass transfer, heat transfer and other functions, and breaks through the limitation that it cannot be applied and developed in the field of directional mass transfer and transmission. At the same time, by compounding the phenolic aerogel matrix and the fiber reinforcement, the contradiction between the high porosity, high specific surface area and high compressive strength of the phenolic aerogel is solved, and the application range of the phenolic aerogel is greatly expanded, and it has a wide application prospect in the fields of ion conductors, environmental purification, filtration and energy catalysis.
[0033] According to some preferred embodiments, the phenolic aerogel precursor for preparing the phenolic aerogel matrix includes a water-soluble phenolic resin, a surfactant, a curing agent, a curing accelerator and water; preferably, the content of the water-soluble phenolic resin in the phenolic aerogel precursor is not more than 10 wt %.
[0034] The present invention selects water-soluble phenolic resin to ensure that it can be evenly dispersed in water, to ensure that the phenolic resin grows in a directional manner during the freezing process, and to form an anisotropic pore structure after freeze-drying.
[0035] According to some preferred embodiments, the mass ratio of the water-soluble phenolic resin to water is 1 to 8:60 (for example, 1:60, 1:30, 1:20, 1:15, 1:12, 1:10, 7:60 or 2:15).
[0036] According to some preferred embodiments, the mass ratio of the surfactant to water is 1 to 6:30 (for example, 1:30, 1:20, 1:15, 1:10, 2:15 or 1:5).
[0037] According to some preferred embodiments, the mass ratio of the curing agent to the water-soluble phenolic resin is 0.5 to 2:5 (for example, it may be 1:10, 0.8:5, 1:5, 1.2:5, 0.3:1, 1.8:5 or 2:5).
[0038] According to some preferred embodiments, the mass ratio of the curing accelerator to the water-soluble phenolic resin is 0.1 to 0.5:1 (for example, it may be 0.1:1, 0.2:1, 0.3:1, 0.4:1 or 0.5:1).
[0039] According to some preferred embodiments, the solid content of the water-soluble phenolic resin is 60-70wt% (for example, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt% or 70wt%).
[0040] According to some preferred embodiments, the water-soluble phenolic resin is a phenolic prepolymer with a molecular weight of 200-800.
[0041] According to some preferred embodiments, the surfactant is a cationic active agent, preferably at least one of hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride.
[0042] The present invention can improve the interfacial dispersibility problem of water and phenolic resin by introducing a cationic surfactant, further improve the dispersibility of phenolic resin in water, and prevent the phenolic resin and ice template from being delaminated during the pre-freezing process, thereby preventing the anisotropic phenolic aerogel from being formed.
[0043] According to some preferred embodiments, the curing agent is a silane coupling agent, preferably at least one of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-mercaptopropyltriethoxysilane and vinyltriethoxysilane.
[0044] According to some preferred embodiments, the curing accelerator is a bicarbonate, preferably at least one of sodium bicarbonate and potassium bicarbonate.
[0045] The present invention adopts a silane coupling agent as a curing agent for the phenolic resin, utilizes its reactivity at low temperatures, and introduces a curing accelerator to reduce the curing temperature of the phenolic resin, thereby avoiding the problem that the pore structure collapses during the curing process due to too high a curing temperature, and the phenolic aerogel with an anisotropic nanopore structure cannot be obtained.
[0046] According to some preferred embodiments, the fiber reinforcement is at least one of chopped fibers, a carbon fiber preform, a quartz fiber preform, a mullite fiber preform, a glass fiber preform, and a porous mullite fiber skeleton; and / or
[0047] The fiber reinforcement is at least one of fiber felt, 2D woven cloth, 2.5D fabric, and 3D fabric.
[0048] In a second aspect, the present invention provides a method for preparing the anisotropic phenolic aerogel composite material according to the first aspect, the preparation method comprising the following steps:
[0049] The fiber reinforcement is impregnated in a phenolic aerogel precursor, and then pre-frozen, freeze-dried and solidified to obtain a phenolic aerogel composite material.
[0050] The present invention places a fiber reinforcement in a phenolic aerogel precursor for impregnation, and then pre-freezes, freeze-dries, and solidifies to obtain a phenolic aerogel composite material. The interfacial dispersibility between water and phenolic resin is improved by a surfactant, the dispersibility of phenolic resin in water is improved, and the stratification problem of phenolic resin and ice template during pre-freezing is prevented; then, the phenolic resin is phase-separated from water along the growth direction of the ice crystal microchannel by directional freezing, and the phenolic resin is phase-separated from water along the growth direction of the ice crystal microchannel, ensuring that the phenolic resin is uniformly dispersed around the ice template, and then the ice template is removed by freeze-drying to achieve the construction of anisotropic nanoporous structure inside the phenolic aerogel, and finally, low-temperature solidification is performed under the promotion of a curing accelerator to obtain a phenolic aerogel composite material with an anisotropic phenolic aerogel structure.
[0051] The traditional phenolic aerogel composite material adopts a preparation process of curing first and then drying. It is an internal disordered pore structure of phenolic nanoparticles accumulated based on the sol-gel polymerization mechanism. The disorder of the internal pores greatly limits its application and development in the field of directional mass transfer and transmission. The present invention first improves the interfacial dispersibility of water and phenolic resin based on surfactants, then phase-separates the phenolic resin from water along the growth direction of the ice crystal microchannel by directional freezing, and then removes the ice template by freeze-drying technology to achieve the construction of an ordered anisotropic pore structure. Finally, the curing temperature of the phenolic resin is reduced by a curing accelerator, and low-temperature curing is performed, which can avoid the collapse of the pore structure due to the high curing temperature during the curing process. Finally, a phenolic aerogel composite material with an ordered anisotropic phenolic aerogel structure is obtained, which improves the directional heat conduction performance of the phenolic aerogel composite material and overcomes the problem that the traditional phenolic aerogel cannot achieve directional mass transfer, heat transfer and other functions.
[0052] The preparation method of the anisotropic phenolic aerogel composite material of the invention has simple process, adopts a water dispersion system, has no pollution to the environment, and realizes the green preparation of the anisotropic phenolic aerogel composite material.
[0053] According to some preferred embodiments, the phenolic aerogel precursor is obtained by mixing phenolic resin, a surfactant, a curing agent and water.
[0054] According to some specific embodiments, the preparation of the phenolic aerogel precursor includes: mixing a surfactant, a curing accelerator and water, and performing ultrasonic treatment (to remove bubbles), and then mixing with a water-soluble phenolic resin to obtain a premixed liquid; mixing the curing agent with the premixed liquid to obtain a phenolic aerogel precursor, wherein the mass ratio of the water-soluble phenolic resin to water is 1 to 8:60, the mass ratio of the surfactant to water is 1 to 6:30, the mass ratio of the curing agent to the water-soluble phenolic resin is 0.5 to 2:5, and the mass ratio of the curing accelerator to the water-soluble phenolic resin is 0.1 to 0.5:1.
[0055] According to some preferred embodiments, the impregnation is vacuum impregnation.
[0056] According to some preferred embodiments, the freeze-drying temperature is -60 to -18°C (for example, it can be -60°C, -55°C, -50°C, -45°C, -40°C, -35°C, -30°C, -25°C, -20°C or -18°C), and the freeze-drying time is 20 to 35h (for example, it can be 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 28h, 30h, 31h, 32h, 33h, 34h or 35h).
[0057] According to some preferred embodiments, the curing temperature is 30-50°C (for example, 30°C, 32°C, 35°C, 38°C, 40°C, 42°C, 45°C, 48°C or 50°C), and the curing time is 15-40h (for example, 15h, 16h, 18h, 20h, 24h, 28h, 30h, 32h, 34h, 36h, 38h or 40h). The curing temperature of the present invention needs to be controlled within the above range. If the curing temperature is too high, the pore structure will collapse during the curing process, and ultimately the phenolic aerogel with anisotropic pore structure cannot be obtained.
[0058] According to some preferred embodiments, the steps of washing and drying are further included after the curing.
[0059] According to some preferred embodiments, the washing is performed by immersion washing with water.
[0060] According to some preferred embodiments, the drying is one or more of normal pressure drying, freeze drying, and supercritical drying.
[0061] After curing, the sample is first soaked and washed with water to remove the surfactant in the sample, and then dried to remove the moisture in the sample, wherein the drying is based on the anisotropic phenolic aerogel composite material maintaining a constant weight.
[0062] According to some specific embodiments, the preparation of phenolic aerogel composite materials includes: (1) pre-freezing: placing the cut fiber preform in a phenolic aerogel precursor and vacuum impregnating it in a mold, and then placing the mold on a pre-cooled freezing device, with the bottom of the mold close to the cold source, and the temperature is directed from the bottom to the top, and directional freezing is performed to form a pre-frozen block with an anisotropic structure; (2) demolding the pre-frozen block and freeze-drying, curing, washing, and drying it to obtain an anisotropic phenolic resin aerogel composite material.
[0063] In order to more clearly illustrate the technical scheme and advantages of the present invention, the present invention is further described below in conjunction with embodiment. The present invention does not specifically limit the source of each reagent adopted in the embodiments and comparative examples, and can directly be purchased or synthesized voluntarily. It should be noted that the phenolic prepolymer of TC-01 purchased from Shandong Shengquan New Material Co., Ltd. is adopted in the following embodiments and comparative examples of the present invention, and the solid content is 69wt%, as water-soluble phenolic resin to illustrate the technical scheme of the present invention, but not limiting, the technical scheme of the present invention can also be realized by adopting other water-soluble phenolic resins.
[0064] Example 1
[0065] (1) Preparation of phenolic resin precursor: First, 8 g of hexadecyltrimethylammonium bromide and 0.2 g of sodium bicarbonate were dissolved in 60 g of deionized water, and 5 g of water-soluble phenolic resin was added and mixed to obtain a premixed solution; then, 1 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added to the premixed solution and mixed to obtain a phenolic aerogel precursor solution;
[0066] (2) Pre-freezing of precursor solution: The cut glass fiber reinforcement is placed in the phenolic aerogel precursor solution and vacuum impregnated in the mold for 30 min, so that the precursor is completely filled with the glass fiber reinforcement. The mold is then placed on a pre-cooled freezing device for pre-freezing. The sample is demolded after it is completely frozen.
[0067] (3) Preparation of anisotropic phenolic aerogel composite material: first, freeze-dry the sample pre-frozen in step (2) at -30°C for 30 h, then cure the freeze-dried sample at 40°C for 30 h, then soak the cured sample in deionized water for 6 h, and finally dry the sample at normal pressure to obtain anisotropic phenolic resin aerogel composite material.
[0068] The scanning electron microscope image of the anisotropic phenolic aerogel composite material prepared in this embodiment is as follows: Figure 2 As shown, the anisotropic phenolic aerogel nanopore structure in the composite material presents a directional and ordered structure. It is precisely because of this wood-like three-dimensional nano-network structure that the material's ability to resist deformation is enhanced to a certain extent. This is also one of the reasons why the mechanical strength of the anisotropic phenolic aerogel is greater than that of traditional phenolic aerogel.
[0069] Example 2
[0070] (1) Preparation of phenolic resin precursor: First, 2 g of hexadecyltrimethylammonium bromide and 0.4 g of potassium bicarbonate were dissolved in 60 g of deionized water, and 1 g of water-soluble phenolic resin was added and mixed to obtain a premixed solution; then, 0.4 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added to the premixed solution and mixed to obtain a phenolic aerogel precursor solution;
[0071] (2) Pre-freezing of precursor solution: The cut glass fiber reinforcement is placed in the phenolic aerogel precursor solution and vacuum impregnated in the mold for 30 minutes, so that the precursor is completely filled with the glass fiber reinforcement. The mold is then placed on a pre-cooled freezing device for pre-freezing. The sample is demolded after it is completely frozen.
[0072] (3) Preparation of anisotropic phenolic aerogel composite material: first, freeze-dry the sample pre-frozen in step (2) at -18°C for 35 h, then cure the freeze-dried sample at 50°C for 15 h, then soak the cured sample in deionized water for 2 h, and finally freeze-dry the sample to obtain an anisotropic phenolic resin aerogel composite material.
[0073] Example 3
[0074] (1) Preparation of phenolic resin precursor: First, 12 g of hexadecyltrimethylammonium bromide and 0.3 g of sodium bicarbonate were dissolved in 60 g of deionized water, and 8 g of water-soluble phenolic resin was added and mixed to obtain a premixed solution; then 2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added to the premixed solution and mixed to obtain a phenolic aerogel precursor solution;
[0075] (2) Pre-freezing of precursor solution: The cut glass fiber reinforcement is placed in the phenolic aerogel precursor solution and vacuum impregnated in a mold for 30 minutes, so that the precursor is completely filled with the glass fiber reinforcement. The mold is then placed on a pre-cooled freezing device for pre-freezing. The sample is demolded after it is completely frozen.
[0076] (3) Preparation of anisotropic phenolic aerogel composite material: first, freeze-dry the sample pre-frozen in step (2) at -25°C for 25 h, then cure the freeze-dried sample at 30°C for 25 h, then soak the cured sample in deionized water for 7 h, and finally supercritically dry the sample to obtain anisotropic phenolic resin aerogel composite material.
[0077] It should be noted that the scanning electron microscope images of the anisotropic phenolic aerogel composite materials prepared in Example 2 and Example 3 are similar to those in Example 3. Figure 2 Similar ones are not listed here one by one.
[0078] Comparative Example 1
[0079] The method is basically the same as Example 1, except that alcohol-soluble phenolic resin is used instead of water-soluble phenolic resin.
[0080] The inventors found that the phenolic aerogel precursor solution could not be frozen into a block during the pre-freezing process in step (2).
[0081] Comparative Example 2
[0082] The method is basically the same as Example 1, except that the surfactant is sodium dodecyl sulfate. The inventors found that when the anionic surfactant sodium dodecyl sulfate is used, the phenolic aerogel precursor solution is delaminated in step (2), with the upper layer being ice and the lower layer being the precipitated phenolic resin.
[0083] Comparative Example 3
[0084] The method is basically the same as Example 1, except that the curing agent is hexamethylenetetramine. The inventors found that the phenolic aerogel cannot be cured in step (3).
[0085] Comparative Example 4
[0086] It is basically the same as Example 1, except that the curing temperature is 70°C.
[0087] The inventors have found that the pore structure in the phenolic aerogel will collapse during the curing process in step (3).
[0088] Comparative Example 5
[0089] The method is basically the same as Example 1, except that the mass of the water-soluble phenolic resin is 12 g.
[0090] The inventors have found that the pore structure in the phenolic aerogel will collapse during the curing process in step (3).
[0091] Table 1. Performance data of phenolic resin aerogel composite materials prepared in the embodiments of the present invention
[0092]
[0093] It should be noted that the thermal conductivity test of the present invention is carried out in accordance with ISO 22007-2 standard. The compressive strength test is carried out in accordance with GB / T 1448-2005, and the compressive strength parallel to the pore structure is tested, and the compressive strength when compressed to 5%. As can be seen from Table 1, the anisotropic phenolic resin aerogel composite material prepared by the present invention has a low thermal conductivity, good thermal insulation performance, and also maintains a high compression resistance.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An anisotropic phenolic aerogel composite material, characterized in that: The anisotropic phenolic aerogel composite material comprises a phenolic aerogel matrix and a fiber reinforcement; the phenolic aerogel matrix is a phenolic aerogel with an anisotropic nanoporous structure; The preparation method of the anisotropic phenolic aerogel composite material comprises: placing a fiber reinforcement in a phenolic aerogel precursor for impregnation, and then pre-freezing, freeze-drying and curing to obtain a phenolic aerogel composite material; the phenolic aerogel precursor for preparing the phenolic aerogel matrix comprises a water-soluble phenolic resin, a surfactant, a curing agent, a curing accelerator and water; the solid content of the water-soluble phenolic resin is 60-70 wt%; the content of the water-soluble phenolic resin in the phenolic aerogel precursor is not more than 10 wt%; the surfactant is at least one of hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride; the curing agent is at least one of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-mercaptopropyltriethoxysilane and vinyltriethoxysilane; the curing accelerator is bicarbonate; the pre-freezing is directional freezing; the curing temperature is 30-50°C and the time is 15-40h.
2. The anisotropic phenolic aerogel composite material according to claim 1, characterized in that: The mass ratio of the water-soluble phenolic resin to water is 1-8:60; The mass ratio of the surfactant to water is 1-6:30; The mass ratio of the curing agent to the water-soluble phenolic resin is 0.5 to 2:5; and / or The mass ratio of the curing accelerator to the water-soluble phenolic resin is 0.1-0.5:
1.
3. The anisotropic phenolic aerogel composite material according to claim 1, characterized in that: The water-soluble phenolic resin is a phenolic prepolymer with a molecular weight of 200-800.
4. The anisotropic phenolic aerogel composite material according to claim 1, characterized in that: The curing accelerator is at least one of sodium bicarbonate and potassium bicarbonate.
5. The anisotropic phenolic aerogel composite material according to claim 1, characterized in that: The fiber reinforcement is at least one of chopped fibers, carbon fiber preforms, quartz fiber preforms, mullite fiber preforms, and glass fiber preforms; and / or The fiber reinforcement is at least one of fiber felt, 2D woven cloth, 2.5D fabric, and 3D fabric.
6. The anisotropic phenolic aerogel composite material according to claim 5, characterized in that: The mullite fiber preform is a porous mullite fiber skeleton.
7. A method for preparing the anisotropic phenolic aerogel composite material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The fiber reinforcement is impregnated in a phenolic aerogel precursor, and then pre-frozen, freeze-dried and solidified to obtain a phenolic aerogel composite material.
8. The preparation method according to claim 7, characterized in that: The impregnation is vacuum impregnation; The freeze drying temperature is -60 to -18°C and the freeze drying time is 20 to 35 hours; and / or After the curing, the method further includes the steps of washing and drying.
Citation Information
Patent Citations
Flexible high flame retardant biologic aerogel material and preparation method thereof
CN109485910A
Low-temperature curing water-based phenolic aerogel composite material and preparation method thereof
CN117683321A
